Interfaith Dialogue and Cultural Engagement: A Community Service Initiative by the TheologyStudy Programfor International Students - Suprianto, Tomi; Kristanto, Kristanto; Lura, Hans; Delianto, Delianto (Yayasan Literasi Kita Indonesia, 2024)
This study aims to investigate how interfaith dialogue and cultural engagement within a community service framework can enhance mutual understanding, foster empathy, and build stronger relationships between international students and local community members. This study applied the qualitative study. This qualitative study employs an interpretive phenomenological approach to explore the lived experiences of international students and local community members involved in the community service initiative. Participants are selected to provide a rich, diverse perspective on the community service initiative: international students, local community members, and faculty and program coordinators. Purposeful sampling is used to select students who have actively participated in various aspects of the initiative, ensuring a range of experiences and viewpoints are represented. Data collection involves multiple qualitative methods to capture a comprehensive view of participants' experiences by using semi-structured interviews and participant observations. Data analysis follows a systematic process to identify and interpret key themes and patterns. Thematic analysis is used to identify, analyze, and report themes within the qualitative data. The study shows that interfaith dialogue and cultural engagement within a community service framework are effective in enhancing understanding, fostering empathy, and building stronger relationships across diverse cultural and religious backgrounds. The initiative has proven to be a valuable model for promoting cohesion and unity in a multicultural setting.